Program Pengentasan Kemiskinan (Tinjauan Bantuan Bibit Babi Di Desa Langgahan Kecamatan Kintamani Kabupaten Bangli, Bali) - Setiawan, Chelsea Rosaline; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Langgahan Village Government provided pig seed assistance as a poverty alleviation program based on community empowernment to their communities categorized as poor households in 2019 as an effort to provide power or strength of economic activity to overcome the poverty problem they faced. This research used a qualitative approach with the type of research is descriptive-explanative. The theory used in this research is the theory of community empowernment by Jim Ife. Based on the result of this research, Langgahan Village Government invited poor households to actively participate in the planning step, the realization step of providing assistance, and the step of developing pig seed assistance. In addition, this research also revealed the factors that influence poor households in developing the pig seed assistance they received until they get a socio-economic impact on their lives. Keywords: Pig Seed Assistance, Poverty Alleviation Porgram, Community Empowernment, Poor Households